1995
DOI: 10.1038/ng0795-288
|View full text |Cite
|
Sign up to set email alerts
|

Acid sphingomyelinase deficient mice: a model of types A and B Niemann–Pick disease

Abstract: Types A and B Niemann-Pick disease (NPD) result from the deficient activity of acid sphingomyelinase (ASM). An animal model of NPD has been created by gene targeting. In affected animals, the disease followed a severe, neurodegenerative course and death occurred by eight months of age. Analysis of these animals showed their tissues had no detectable ASM activity, the blood cholesterol levels and sphingomyelin in the liver and brain were elevated, and atrophy of the cerebellum and marked deficiency of Purkinje … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
405
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 456 publications
(419 citation statements)
references
References 28 publications
14
405
0
Order By: Relevance
“…Untreated ASMKO mice have Ͻ1% of normal WBC ASM activity. 9 Beginning at 1 month and up until the fifth month after transplant, the levels of WBC ASM activity in the treated animals progressively increased, and stabilized thereafter. However, no direct correlation between the WBC ASM activity and survival (see Figure Figure 1 2, below) was observed when individual animals were analyzed.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Untreated ASMKO mice have Ͻ1% of normal WBC ASM activity. 9 Beginning at 1 month and up until the fifth month after transplant, the levels of WBC ASM activity in the treated animals progressively increased, and stabilized thereafter. However, no direct correlation between the WBC ASM activity and survival (see Figure Figure 1 2, below) was observed when individual animals were analyzed.…”
Section: Resultsmentioning
confidence: 96%
“…9,18,25 It is also the likely cause of the progressive ataxia, which eventually leads to death. It has been reported that ceramide is an essential factor required for survival of cerebella PC neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations